1986
DOI: 10.1080/03601238609372508
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and metabolism of Oxamyl and phenamiphos in soils

Abstract: Degradation and metabolism of the nonvolatile nematicidesinsecticides [ 14 C]oxamyl and [ 14 C]phenamiphos (P) were investigated using three Southeastern U.S. soils (Arredondo sand, Cecil sandy loam and Grenada silt loam). Oxamyl in moist soils (10 and 33 kPa) was rapidly mineralized to CO 2 , with N,N-dimethyl-2-(methylthio)acetamide oxime (DMAO) being the major intermediate metabolite. Half-lives (t ½ ) for extractable 14 C in [ 14 C]oxamyl treated soils ranged from 8 to 50 d. Although the principal 14 C com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Considerable amounts of aldicarb sulphone were also detected in all surface samples, whereas negligible amounts of aldicarb sulphone were detected in all subsurface samples. The results confirmed that the oxidation and hydrolysis of aldicarb in surface soil occurred more rapidly than it did in the subsurface soil (Ou & Rao, 1986). A given pesticide's likelihood of reaching the groundwater is affected by the degradation rates in the subsurface, as well as in the surface layers, of the unsaturated soil zone (Bromilow et al, 1986;Pothuluri et al, 1990;Bergstrom, 1996).…”
Section: Soil Depthsupporting
confidence: 73%
See 2 more Smart Citations
“…Considerable amounts of aldicarb sulphone were also detected in all surface samples, whereas negligible amounts of aldicarb sulphone were detected in all subsurface samples. The results confirmed that the oxidation and hydrolysis of aldicarb in surface soil occurred more rapidly than it did in the subsurface soil (Ou & Rao, 1986). A given pesticide's likelihood of reaching the groundwater is affected by the degradation rates in the subsurface, as well as in the surface layers, of the unsaturated soil zone (Bromilow et al, 1986;Pothuluri et al, 1990;Bergstrom, 1996).…”
Section: Soil Depthsupporting
confidence: 73%
“…Blumhorst (1996) suggested that the increase might be due to increased microbial activity in such soils. Ou and Rao (1986) reported that the total toxic residue of fenamiphos disappeared more rapidly in moist soil than in dry soil. At high soil-moisture levels, nematicidal compounds were more easily dissolved and dispersed, and therefore were more available for both chemical and microbial breakdown.…”
Section: Soil Moisturementioning
confidence: 99%
See 1 more Smart Citation
“…The targeted amount of fenamiphos applied in the field ranges between 10 and 45 mg kg -1 soil, which results in the use of 6-10 kg ha -1 under practical conditions depending on the crop. The halflife of fenamiphos has been reported to be 63 days (Ou and Rao 1986), although degradation of this nematicide in 14 days or less has been observed in soils with a history of repeated exposure ; Davis et al 1993). …”
Section: Introductionmentioning
confidence: 93%
“…They were maintained under laboratory conditions in the dark at 14±1ºC. The targeted amount of fenamiphos applied in the field ranges from 10 to 45 mg/kg soil which results in the use of 6-10 kg/ha under practical conditions depending on the crop [16,17]. It was reported that normal field application rates of fenamiphos can vary between 0.5 and 10 kg/ha, equivalent to 5 and 100 mg/kg soil [18,19].…”
Section: Methodsmentioning
confidence: 99%